Aerodynamic model of propeller–wing interaction for distributed propeller aircraft concept. (August 2020) - Bohari, Baizura; Borlon, Quentin; Bronz, Murat; Benard, Emmanuel
The present investigation addresses two key issues in aerodynamic performance of a propeller–wing configuration, namely linear and nonlinear predictions with low-order numerical models. The developed aerodynamic model is targeted to be used in the preliminary aircraft design loop. First, the combination of selected propeller model, i.e. blade element theory with the wing model, i.e. lifting line theory and vortex lattice method is considered for linear aerodynamic model. Second, for the nonlinear prediction, a modified vortex lattice method is paired with the two-dimensional viscous effect of the airfoils to simplify and reduce the computational time. These models are implemented and validated with existing experimental data to predict the differences in lift and drag distribution. Overall, the predicted results show agreement with low percentage of error compared with the experimental data for various thrust coefficients and produced induced drag distribution that behaves as expected.